Fractionation and immunoreactivity of Mycobacterium hovis AN5 culture filtrate antigens - GUPTA, V C; RAM, G C (The Indian Journal of Animal Sciences, 2014)
Protein secreted by Mycobacterium species have been suggested as major immune targets, Four weeks old M, bovis AN5 culture filtrate protein antigens were fractionated by gel permeation and anion exchange chromatography, These fractionoted antigcns WCIC evaluated for theirreactivity to anti M bovis AN5 antiserum in ELISA, Out of several fractionated antigens, the more reactive antigens were heterogenous polypeptides of 46,42,40 and 38 kDa and homogenous polypeptides of 48 and 17.4 kDa molecular masses, Western immunoblot analysis of crudc culturc filtrate antigens revealed 9 reactive bands of 74,48,46,43, 38,23,21.4,17,4 and 14 kDa molecular masses. Most of the fretionated culture fillmtc antigens showcd cross- reactivity with other Mycobacterium species in ELISA except 17.4 kDa antigen that showed species specificity to M. bovis AN5, It is concluded that some of the culture filtrate antigens are highly immunogenic for humoral response.